High-power DC-DC converter based on SiC power device - MA Hou-cheng; ZHOU Xiao-min; GAO Da-wei (工程科学学报)
The DC-DC converter can adjust and control the voltage and power outputs of renewable energy systems, including fuel cell and photovoltaic cell systems. This study used high-efficiency SiC MOSFETs in a two-phase interleaved boost-type DC-DC converter in fuel cell vehicles. This paper analyze the performance of the converter with the SiC power device, based on calculation, simulation, and experimental results. The results show that the application of new SiC devices in high-power DC-DC converters can improve the power density, converter reliability, and power system efficiency. The results can be used for reference in the application of new power electronic devices and related research in the renewable energy filed.